1983
DOI: 10.1271/bbb1961.47.299
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of trimeric lignin model compounds, arylglycerol-.BETA.-syringaresinol ethers, by Fusarium solani M-13-1.

Abstract: Trimeric lignin model compounds, arylglycerol-/?-syringaresinol ethers, were incubated with Fusarium solani M-1 3-1 in basal salts mediumwith shaking. From the culture filtrates, degradation products were isolated and characterized spectroscopically. Based on the degradation products of guaiacylglycerol-/?-syringaresinol ether (II), the following reactions were found to occur; 1) oxidation of benzylic position (a") and subsequent ring opening of the syringaresinol side chain, 2) cleavage of alkyl-aryl CC bonds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 2 publications
0
15
0
1
Order By: Relevance
“…The MS fragmentation patterns indicated that compounds I and II were fairly symmetrical, showing the most abundant mass fragment at m/z 181. This fragment was assigned to the 3,5-dimethoxy,4-hydroxy-␣-ketone moiety (Iwahara, 1983;Kamaya et al, 1983). In addition, the appearance of fragments of 44, 402, and 358 in the mass spectra suggested a presence of one and two decarboxylated molecules, respectively.…”
Section: Characterization Of Products From Phase a Of Sa Transformationmentioning
confidence: 99%
“…The MS fragmentation patterns indicated that compounds I and II were fairly symmetrical, showing the most abundant mass fragment at m/z 181. This fragment was assigned to the 3,5-dimethoxy,4-hydroxy-␣-ketone moiety (Iwahara, 1983;Kamaya et al, 1983). In addition, the appearance of fragments of 44, 402, and 358 in the mass spectra suggested a presence of one and two decarboxylated molecules, respectively.…”
Section: Characterization Of Products From Phase a Of Sa Transformationmentioning
confidence: 99%
“…These oxidative changes in compost lignins may be catalyzed by mushroom laccase through a hydroxyl radical mechanism, probably a one-electron oxidation (11,53). In vitro experiments using lignin model compounds have shown that fungal laccase catalyzes certain degradation reactions (61), particularly with syringyl compounds (30,32,33,43), and can also cause C.-C,3 cleavage in phenolic syringyl units to produce benzoic acid structures (35).…”
mentioning
confidence: 99%
“…Les premieres etudes de modelisation de la lignine effectuees ä partir d'oligolignols sont relativement recentes (Kamaya et al 1983). Par leur developpement des informations complementaires devraient etre apportees ä celles obtenues essentiellement ä partir de monomeres et de dimeres mais qui sont representatifs d'une seule unite structurale de base du biopolymere.…”
Section: Resultsunclassified